Real-world effectiveness of goserelin 10.8-mg compared to goserelin 3.6-mg in premenopausal and perimenopausal Chinese patients with hormone receptor positive breast cancer: a cohort study - Yongsheng Wang; Xi Wang; Jiong Wu; Hong Liu; Jiuda Zhao; Jian Huang; Jianxia Liu; Youling Gong; Hao Wang; Huaqing Yang; Guorong Zou; Quchang Ouyang; et al. (Journal of the National Cancer Center)
Background: Few studies compared the effectiveness of the 3-monthly goserelin 10.8-mg and the monthly 3.6-mg depot in inducing ovarian function suppression for premenopausal patients with hormone receptor positive (HR+) breast cancer. We conducted a large-scale real-world study (RWS) in China to validate the non-inferiority of goserelin 10.8-mg to the 3.6-mg depot. Methods: This multicenter, retrospective-prospective, non-inferiority study compared goserelin 10.8-mg with 3.6-mg in suppressing estradiol (E2) levels in premenopausal and perimenopausal patients with HR+ breast cancer. Eligible patients were identified, and their demographic and clinical data were obtained from hospital medical records. The observation period was 28 weeks. Propensity score matching (PSM) ensured baseline comparability. The primary endpoint was the proportion of patients with E2 suppression to postmenopausal level at Week 12±4. Difference in proportions and 95 % CI was calculated by Newcombe-Wilson score method. The non-inferiority margin was -10 %. Subgroup and sensitivity analyses assessed result robustness. Results: From 1st January, 2015 to 15th December, 2023, 15,629 patients from 16 hospitals nationwide were screened, with 1,060 eligible patients included in the full analysis set (3.6-mg group: 678; 10.8-mg group: 382). Post-PSM, the primary endpoint was analyzed in 590 patients (295 in each group). At Week 12±4, the proportion of patients with E2 suppression was 99.1 % (95 % CI: 96.9 %–99.8 %) for goserelin 10.8-mg and 95.3 % (95 % CI: 91.0 %–97.6 %) for goserelin 3.6-mg. The difference was 3.8 % (95 % CI: 0.6 %–8.1 %) with the lower limit of 95 % CI greater than the non-inferiority margin. All subgroup analyses, including those based on age (≤45 or >45 years) and previous chemotherapy (yes/no), and all sensitivity analyses on the primary endpoint were consistent with the main analysis. Conclusions: This RWS validated the non-inferiority of goserelin 10.8-mg 3-monthly to 3.6-mg monthly in Chinese patients with HR+ breast cancer, where high E2 suppression rates were achieved in both goserelin dosage groups. Trial registration: ClinicalTrials.gov (NCT05184257).